High prevalence of functional dyspepsia in nonalcoholic fatty liver disease: a cross-sectional study - Lima, Érika Cristina (2022)
BACKGROUND: Gastrointestinal (GI) symptoms are frequent complaints from individuals with nonalcoholic fatty liver disease (NAFLD). Dyspepsia is a universal clinical symptom and is among the most common GI complaints observed in the general population, but its prevalence in the population with NAFLD has not been previously investigated. OBJECTIVE: To compare the prevalence of functional dyspepsia (FD) between patients with NAFLD and controls without liver disease. DESIGN AND SETTING: Cross-sectional study at the Outpatient Liver Clinic, University Hospital, Belo Horizonte, Brazil. METHODS: We included 96 NAFLD patients and 105 controls without liver disease. All participants were assessed for GI symptoms in accordance with the Rome III criteria. Evaluation methods included a questionnaire for FD (validated in Brazil), laboratory tests and upper GI endoscopy. RESULTS: Mean age and sex were similar between the groups. The NAFLD group presented higher frequency of proton-pump inhibitor usage (31.3% vs 4.8%; P < 0.001) and prevalence of FD (25.0% versus 12.4%; P = 0.021). The symptom frequencies were as follows: postprandial distress, 22.9% versus 11.4% (P = 0.030); postprandial fullness, 18.8% versus 10.5% (P = 0.095); early satiation, 8.3% versus 5.7% (P = 0.466); and epigastric pain or burning, 18.8% versus 5.7% (P = 0.004), in NAFLD patients and controls, respectively. Multivariate analysis demonstrated that female sex (odds ratio, OR 6.97; 95% confidence interval, CI: 1.51-32.12; P = 0.013) and NAFLD diagnosis (OR 2.45; 95% CI: 1.14-5.27; P = 0.021) were independently associated with FD occurrence. CONCLUSION: FD occurs more frequently in individuals with NAFLD than in controls without hepatic disease.